2023
DOI: 10.1021/acs.jpcc.2c08575
|View full text |Cite
|
Sign up to set email alerts
|

Thousand-Fold Enhancement of Photothermal Signals in Near-Critical CO2

Abstract: Photothermal (PT) microscopy has shown strong promise in imaging single absorbing nano-objects in soft matter and biological systems. PT imaging at ambient conditions usually requires a high laser power for a sensitive detection, which prevents application to light-sensitive nanoparticles. In a previous study of single gold nanoparticles, we showed that the photothermal signal can be enhanced more than 1000-fold in near-critical xenon compared to that in glycerol, a typical medium for PT detection. In this rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Larger dielectric nanoparticles or carefully designed nanoparticle assemblies/clusters with multiple resonances could also be used in a 2-fold manner: at one wavelength, they could provide a near-field for enhanced absorption of chiral molecules, and at a second wavelength, they could be used to sensitively probe the refractive index change induced by molecular differential absorption. Recent work using supercritical CO 2 for photothermal detection 36 has shown great improvement in sensitivity for PT imaging and could be combined with the aforementioned approaches, but the use of CO 2 would limit biochemical applications.…”
Section: ■ Basic Principle Of Pt MCD Microscopymentioning
confidence: 99%
“…Larger dielectric nanoparticles or carefully designed nanoparticle assemblies/clusters with multiple resonances could also be used in a 2-fold manner: at one wavelength, they could provide a near-field for enhanced absorption of chiral molecules, and at a second wavelength, they could be used to sensitively probe the refractive index change induced by molecular differential absorption. Recent work using supercritical CO 2 for photothermal detection 36 has shown great improvement in sensitivity for PT imaging and could be combined with the aforementioned approaches, but the use of CO 2 would limit biochemical applications.…”
Section: ■ Basic Principle Of Pt MCD Microscopymentioning
confidence: 99%
“…This work has been made possible by the previous research, which showed the ability of nanomechanical resonators to detect and quantify the absorption of single plasmonic and polymer nanoparticles via photothermal heating. It is worth noting that this photothermal spectromicroscopy approach is not based on the thermo-optical effect as in photothermal contrast microscopy, , where the absorber is detected due to the temperature dependence of the surrounding embedding medium refractive index (glycerol, thermotropic liquid crystal, near-critical Xe or CO 2 ) , via modulation of the scattering of a second probing laser. In nanomechanical photothermal spectromicroscopy, this thermal effect consists instead of a stress reduction in the nanomechanical resonator, detuning its resonance frequency upon illumination of the nanoabsorber.…”
Section: Introductionmentioning
confidence: 99%